2020
DOI: 10.3390/v12101183
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Study about the Dispersal Patterns of the Predominant HIV-1 Subtypes A1 and B in Greece: Inference of the Molecular Transmission Clusters

Abstract: Our aim was to investigate the dispersal patterns and parameters associated with local molecular transmission clusters (MTCs) of subtypes A1 and B in Greece (predominant HIV-1 subtypes). The analysis focused on 1751 (28.4%) and 2575 (41.8%) sequences of subtype A1 and B, respectively. Identification of MTCs was based on phylogenetic analysis. The analyses identified 38 MTCs including 2–1518 subtype A1 sequences and 168 MTCs in the range of 2–218 subtype B sequences. The proportion of sequences within MTCs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…Our study population consisted of PLHIV with known transmission dates from the following datasets: i) a “seek-test-treat” intervention programme named “ARISTOTLE” implemented in Athens, Greece, during 2012-2013 (14), ii) a network-based intervention that targeted persons with recent HIV-infection (“TRIP”) implemented in Athens, Greece, between 2013 and 2015 (15), iii) PLHIV infected within a subtype A1 MTC in Greece (16, 17), iv) People who inject drugs (PWID) infected locally during an HIV outbreak in Luxembourg since 2014 and v) PLHIV infected within a CRF42_BF MTC in Luxembourg (18) (Table 1). HIV sequences were selected to belong to PWID-specific MTCs [datasets (i), (ii) and (iv)] and local MTCs [datasets (iii) and (v)] (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study population consisted of PLHIV with known transmission dates from the following datasets: i) a “seek-test-treat” intervention programme named “ARISTOTLE” implemented in Athens, Greece, during 2012-2013 (14), ii) a network-based intervention that targeted persons with recent HIV-infection (“TRIP”) implemented in Athens, Greece, between 2013 and 2015 (15), iii) PLHIV infected within a subtype A1 MTC in Greece (16, 17), iv) People who inject drugs (PWID) infected locally during an HIV outbreak in Luxembourg since 2014 and v) PLHIV infected within a CRF42_BF MTC in Luxembourg (18) (Table 1). HIV sequences were selected to belong to PWID-specific MTCs [datasets (i), (ii) and (iv)] and local MTCs [datasets (iii) and (v)] (19).…”
Section: Methodsmentioning
confidence: 99%
“…HIV sequences were selected to belong to PWID-specific MTCs [datasets (i), (ii) and (iv)] and local MTCs [datasets (iii) and (v)] (19). Local MTCs were defined as phylogenetic clusters including ≥ 2 sequences from the same geographic area (Greece or Luxembourg) at a proportion greater than 70% compared to the total number of sequences within the cluster, as previously described in detail (16, 20). All sequences were generated before the ARV treatment initiation.…”
Section: Methodsmentioning
confidence: 99%
“…Although HIV-1 cases declined after 2012, the proportion of diagnoses among PWID remained higher (i.e., between 16.0% and 17.9%) than before the outbreak (around 5%) (https://eody.gov.gr/, accessed on 15 September 2021). Our previous analysis, using a dense sample of sequences from HIV-1 individuals sampled during 1999-2015, showed that the subtypes A1 and B were the most prevalent clades in Greece [22]. Regarding the patterns of HIV-1 transmission, 93.8% and 77.0% of sequences for subtype A1 and B, respectively, were found to belong within local clusters [22].…”
Section: Introductionmentioning
confidence: 98%
“…Traditionally, subtyping has been used to monitor viral genetic diversity and to map the distribution of HIV-1 clades across different geographic areas. Sophisticated phylogenetic and phylodynamic analyses have been implemented to investigate the characteristics of HIV dispersal (identification of clusters) and to estimate the clusters' transmission dynamics over time [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…A time-space cluster occurs by focusing on the identification of MTCs in a particular geographic area while using time-reversible phylodynamics approaches. MTCs have been used to examine the likely impact of genetic (mutations and subtypes of viruses) [ 27 , 28 , 29 ], demographic and clinical [ 22 , 25 , 26 ] factors on regional phylogenetic clustering. Identification of MTCs for HIV has resulted in the characterization of the risk factors that are associated with the spread of the virus in different countries [ 22 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%